Tokyo's booms and busts: Placing Japan in the global financial network - Liam Keenan; Dariusz Wójcik (Finance and Society, 2022)
Tokyo is conspicuous for its now decades-long absence in the headlines of global financial news. In this article, we revisit the evolution of Tokyo as an international financial centre through the lens of Global Financial Networks (GFN). Drawing on insights from high-level interviews, we present a chronology of Japan's financial history between 1980 and 2020. This reveals a pattern wherein financial sector reforms and financial centre initiatives are repeatedly interrupted by crises. The GFN framework helps to demonstrate how structure and agency intertwine at the global, national, and local scales to shape this reform-boosterism- crisis cycle. Nationally and locally, we find that despite repeated attempts by coalitions of actors to elevate the status of Tokyo, engrained cultural and political economic conditions have hindered its development into a truly global financial centre. Globally, these conditions have been structured and amplified by Japan's historical position as a rule-taker in the governance of international finance. These factors have conspired to situate Japan on the periphery of the GFN, a position aggravated by the rising financial power of China.
Keywords: 300; Financial centres; global financial networks; Japan; Tokyo